The Image of Ibrahim Pasha in Early Modern English Drama: Thomas Kyd’s The Tragedy of Soliman and Perseda - Gülter, Işıl Şahin (My University, 2019)
In The Tragedy of Soliman and Perseda, Thomas Kyd tends to portray Sultan Suleyman’s reign in the context of sixteenth century Ottoman - European relations. In the aftermath of Sultan Suleyman’s succession to the throne, Ottoman Empire expands its borders towards European territories conquering strategic holds such as Belgrade, Rhodes and Buda. Ottoman westward expansion increases cultural interaction between the Ottomans and the Europeans. More specifically, Ottoman presence in the Mediterranean stimulates Anglo-Ottoman relations. As a result of cultural interaction, the English playwrights frequently people their plays with Ottoman characters and historical episodes. Especially Sultan Suleyman, called ‘Magnificent’ in Europe, is widely depicted on the English stage. However, in this study, it is aimed to analyze Kyd’s Erastus character constructed on the historical figure Ibrahim Pasha, since Ibrahim Pasha is regarded as one of the prominent figures of Sultan Suleyman’s reign. Ibrahim, who is presented to the service of Suleyman in the years of his princely governorate in Manisa, becomes Suleyman’s ‘favorite’ in a very short time. In the aftermath of Suleyman’s succession to the throne in 1520, Ibrahim is conferred respectively honors of hasodabaşı, içşahincilerağası, grand vizier and beylerbeyi. Besides, Ibrahim is endowed with privileges that were never granted to the prior grand viziers. Nevertheless, at the peak of power and strength, he is summoned to the palace and executed. In Kyd’s play, Erastus is also presented to the service of Suleyman as a war captive. They bound such an intimate relationship that Erastus is appointed to the highest ranks in the government and granted with many privileges. However, he is accused of treason and executed at the end of the play. Ultimately, this study aims to analyze the image of Ibrahim Pasha represented as Erastus character in Kyd’s The Tragedy of Soliman and Perseda.
Keywords: Tarih; Ortaçağ ve Rönesans Çalışmaları; Edebiyat